THE EFFECT OF STRATEGIC PLANNING ON EFFECTIVENESS OF ACADEMIC ENTERPRISE - M. Rabee, Ahmad M. Rabee (European Scientific Journal, ESJ, 2014)
Strategic planning is considered very crucial in educationalorganizations. Strategic planning has direct impact on educational output.The objective of this study is to examine the effect of strategic planning onacademic enterprise. To achieve this objective, questionnaire was used andfinancial data was collected. The results of this research indicated thatstrategic planning affects the effectiveness of academic enterprise.